A study of the influence of talent management practices on employee performance among state government employees in Kelantan - Mat Zin, Sakinah; Nik Md Salleh, Nik Sarina; Abdullah, Iskandar Hasan Tan; Wan Sulaiman, Wan Ahmad Tirmizi (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Managers of global organizations and businesses now consider talent management (TM) as a vital strategic area. Therefore, this study aimed to examine the impact of talent management practices, such as talent acquisition, talent development and talent retention on the job performance of State Government employees in Kelantan. This study gathered data from 385 employees using a self-administered survey questionnaire and applied a convenience sampling approach. This study tested its hypotheses through tests of validity and reliability and multiple regression analysis. The study found that talent management has a positive and significant impact on employee performance. However, contrary to previous research, the study concluded that developing employees does not have a significant effect on employee performance. Additionally, the research found a significant statistical correlation between acquisition, retention, and employee performance. Furthermore, this study focused on talent management practices and job performance among employees of the Kelantan State Government, which provides a valuable contribution to this area of study. The study can serve as a resource for public sector managers, providing suggestions on how to enhance employee performance through implementing talent management practices.